ANALISIS TINGKAT KEPUASAN MAHASISWA ATAS KUALITAS PELAYANAN AKADEMIK PADA PRODI S1 MANAJEMEN FEB UNIVERSITAS RIAU - Muhamad Naufal Mustakim; Jushermi Jushermi; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the level of student satisfaction with thequality of academic services in the Management Study Program FEB UNRI.The population in this study were all active undergraduate managementstudents with a sample of 100 students using simple random samplingtechnique. The data analysis used is IPA (importance performance analysis)with the SPSS program. The results showed that the level of satisfaction ofstudents majoring in S1 Management FEB UNRI from the dimensions ofreliability, responsiveness, assurance, empathy, tangible was quitesatisfactory. The strategy used to increase student satisfaction majoring inS1 Management FEB UNRI is a service recovery strategy where thedepartment learns to deal with every problem and learn from failure, aswell as make continuous improvements and improvements. Keyword : Tangible, Reability, Responsivness, Assurance, Emphaty